Field notes contributed by Paul Martsching for Story County, summer 1984 - Martsching, Paulet al (1984)
Field notes were contributed by Paul Martsching for Story County, summer 1984. Among 26 species sighted, Pied-billed Grebes and Coots were observed feeding their young at Larson Marsh or near Colo, and a Peregrine Falcon in Ames was documented. Greater and Lesser Yellowlegs were seen together near Ames and Colo. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1984. Epson - sheet feed